2010
DOI: 10.1007/s12564-010-9132-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of rate of returns for postgraduate education in Taiwan: the impact of higher education expansion

Abstract: This paper analyzes the dynamics of rate of returns for postgraduate education and the determinants of wage premiums for postgraduate labor, especially for the impact of higher education expansions, in terms of quantity and quality, since the late 1990s in Taiwan. Utilizing quasipanel data over the 1990-2004 period and employing the double fixed effect model, the empirical results first confirm the existence of wage premiums for workers with postgraduate degrees. However, the analysis on the dynamics of wage p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…If a large proportion of candidates for a college degree, even though well prepared, decide to opt out, the overall quality of the labor force would become lower. Meanwhile, if most qualified college graduates decide to postpone entering the job market, the match between education and the labor market for society would not be efficient and, thus, there would be a waste of social resources, or 'over-education' (Yang et al, 2011). Therefore, how to maintain a considerable level of returns to a college degree may be one of the focuses of education-related policies.…”
Section: Discussionmentioning
confidence: 99%
“…If a large proportion of candidates for a college degree, even though well prepared, decide to opt out, the overall quality of the labor force would become lower. Meanwhile, if most qualified college graduates decide to postpone entering the job market, the match between education and the labor market for society would not be efficient and, thus, there would be a waste of social resources, or 'over-education' (Yang et al, 2011). Therefore, how to maintain a considerable level of returns to a college degree may be one of the focuses of education-related policies.…”
Section: Discussionmentioning
confidence: 99%
“…Some academic studies indicate that such a universal system has negative impacts on graduates' income level. For example, Yang et al ( 2011 ) investigate the rate of returns to postgraduate education in Taiwan during the 1990-2004 period. Although they confi rm the positive return to these students ranging from 1.40 to 11.67 %, they also fi nd that 'the sharp increase in the supply of postgraduate labour appears to have a negative impact on an individual's wage premium ' (p. 359).…”
Section: Expansion As An Intermediate Factormentioning
confidence: 99%
“…In this new century, numerous empirical studies have continued to analyze the disciplinary differences of educational returns and learner's income (Saha & Sensarma, 2011;Salas-Velasco, 2006;Thomas, 2000;Yang et al, 2011). Bell (2010) found that graduate students who majored in science, technology, engineering, and mathematics earned more than those who did not.…”
mentioning
confidence: 99%